The Relationships Between the Free-Living and Particle-Attached Bacterial Communities in Response to Elevated Eutrophication - Hu, Yang; Xie, Guijuan; Jiang, Xingyu; Shao, Keqiang; Tang, Xiangming; Gao, Guang (Frontiers in Microbiology, 2020)
Exploring the relationships between free-living (FL) and particle-attached (PA) bacterial communities can provide insight into their connectivity, and the partitioning of biogeochemical processes, which is crucial to understanding the elemental cycles and metabolic pathways in aquatic ecosystems. However, there is still intense debate about that whether FL and PA fractions have the same assemblage. To address this issue, we investigated the extent of similarity between FL and PA bacterial communities along the environmental gradients in the Lake Wuli, China. Our results revealed that the west Lake Wuli was slightly eutrophic, and the east lake was moderately and highly eutrophic. The alpha-diversity of the FL bacterial communities was significantly lower than that of the PA fraction in the west lake, whereas the alpha-diversity of the two fractions was comparable in the east lake. The beta-diversity of both communities significantly differed in the west lake, while they resembled in the east lake. Moreover, functional prediction analysis highlighted the significantly larger differences of metabolic functions between the FL and PA fractions in the west lake than in the east lake. Suspended particles and carbon resource promote the similarity between the FL and PA fractions. Collectively, our result reveals a convergent succession of aquatic communities along the eutrophic gradient, highlighting that the connectivity between FL and PA bacterial communities is nutrient-related.